Constrained tree growth and gas exchange of seawater‐exposed forests in the Pacific Northwest, USA. (27th June 2019) - Wang, Wenzhi; McDowell, Nate G.; Ward, Nicholas D.; Indivero, Julia; Gunn, Cailene; Bailey, Vanessa L.
Abstract: Rising sea levels under climate change may have significant impacts on coastal vegetation dynamics, yet the response of coastal forest growth, gas exchange and survival to seawater intrusion remains poorly documented. We conducted a dendroecology study across six sites in western Washington, USA, to examine how tree growth, gas exchange (indexed by basal area increment ( BAI) and wood δ 13 C respectively), and survival varies with seawater exposure through two approaches. First, tree core samples were collected at a site where seawater exposure started only 4 years prior to sampling, which allowed a cause‐and‐effect test of the impacts of seawater exposure on trees, and second, samples were collected at five additional sites where we compared downstream to upstream trees under current sea‐level conditions. At the seawater intrusion site, BAI and carbon isotope discrimination (Δ) decreased significantly ( p  < 0.01) in the year of intrusion (2014) and stayed unchanged thereafter. Four years later (2018), the percentage of recently standing dead trees in the forest was 73.0% of the basal area. Across the regional assessment, percentage of standing dead trees was significantly greater in downstream than upstream forests at five of the six sites (averaged 37.7 ± 11.0% and 4.3 ± 2.1% basal area for downstream and upstream, respectively). Growth was significantly lower ( p  < 0.01) at the downstream than upstream for five sites, and Δ was lower for all needle‐leaf trees (three sites) on the downstream compared to the upstream, but no difference was observed between downstream and upstream for broad‐leaf trees (three sites). Synthesis . Combined both the cause‐and‐effect manipulative study and the regional assessment demonstrate that seawater exposure drives reductions in growth, decreased Δ of needle‐leaf trees, increased mortality and greater climate sensitivity, regardless of whether the seawater exposure is recent or long‐term. Abstract : To examine how coastal forests respond to rising sea levels, we conducted a dendroecology study across six sites in western Washington, USA. Combined, both the cause‐and‐effect manipulative study and the regional assessment demonstrate that seawater exposure drives reductions in growth, decreased stomatal conductance, increased mortality, and greater climate sensitivity, regardless of whether the seawater exposure is recent or long term.